A Closer Look at the 2013 to 2014 Integrated Plastic Surgery Match. Issue 3 (March 2016) - Kling, Russell E.; Kling, Rochelle R.; Agi, Chika; Toirac, Alexander; Manders, Ernest K.
Abstract : Background: Plastic surgery has become an increasingly competitive, yet limited information is available in the literature on successfully matched plastic surgery applicants. The goal of this study was to analyze which factors predicted a successful National Residency Match Program match during the 2013 to 2014 cycle. Methods: An electronic questionnaire was distributed to successfully matched medical students in plastic surgery. Information obtained included (1) academic performance, (2) medical school criteria, (3) visiting subinternship rotation criteria, and (4) research performance. Match "success" was defined as matching into one of the applicant's top three ranked programs Results: Data were available for 127 matched students. Average Step 1 score was 247.93 (95 percent CI, 244.3 to 251.56). Step 1 scores correlated with the number of interviews received ( r 2 = 0.355; p = 0.039). An odds ratio of 2.2 was observed for residents who had a plastic surgery residency program affiliated with their medical school and match success. Step 1 score ( r 2 = 0.045; p = 0.798), Step 2 score ( r 2 = 0.131; p = 0.505), Alpha Omega Alpha membership ( r 2 = 0.011; p = 0.905), and number of publications ( r 2 = 0.121; p = 0.458) did not correlate significantly with match success. Conclusions: Successful applicants had a Step 1 score that was 1 SD greater than the U.S. mean. Having a plastic surgery residency program affiliated with an applicant's medical school was an important predictor of match success. Objective measures (step scores, Alpha Omega Alpha membership, and number of publications) were not predictive of match success.